Restoration of Bile Outflow in Case of Damage to Hepaticocholedochus and Failure of the Biliary Anastomosis After Laparoscopic Cholecystectomy - A. V. Novozhilov; M. O. Movsisyan; S. E. Grigoryev (Неотложная медицинская помощь, 2022)
The aspect of injuring bile ducts during laparoscopic cholecystectomy is still of current concern. Causes of this complication include insufficient experience of surgical team, poor knowledge of topographic anatomy of subhepatic space, particularly when perivesical inflammatory infiltrate presents, inadequate approach conversion and so on. Most of patients with bile duct injuries undergo repeated operation in the same surgical unit where cholecystectomy was performed. In many cases, this results in a shortening of the segment of the common hepatic duct, which is favorable for restoration. Subsequent reconstructive surgery is usually performed in the worse conditions with a high risk of complications such as failure of sutures, biliary fistula, anastomotic stricture, etc. Most specialists recommend to abstain from primary reconstruction of the biliary tree in hospitals with no proper experience in hepatobiliary surgery and to perform only the external drainage of subhepatic space with subsequent admission of patient to a specialized clinic. We report a case of a young woman who suffered an excision of hepaticocholedochus fragment during laparoscopic cholecystectomy. A primary reconstructive surgery (hepatico-hepaticoanastomosis) was performed in the same clinic and resulted in external fistula of the common hepatic duct. The subsequent operation (hepaticoejunostomy) was performed in a specialized department of the regional clinical hospital. The woman underwent right-sided hypochondrium laparotomy with debridement of postoperative scar tissues. The stumps of common bile duct were mobilized in compact inflammatory infiltrate. The operation ended with distal stump closure and hepaticoenteroanastomosis formation. The patient was discharged with recovery. Six months later, her condition was satisfactory, and she was engaged in occupational activity.